GAGASAN REFORMASI BIROKRASI DALAM RANCANGAN UNDANG UNDANG (RUU) TENTANG ADMINISTRASI PEMERINTAHAN - Indiahono, Dwiyanto (Jurnal Dinamika Hukum, 2011)
Draft of Public Administration Law in the reality is arranging how public administration done by government and citizen. This draft is legal fundament to put down public functionary rights and obligations, governmental institution (as public organization) and public as citizen more equal. Bureaucracy reform have to be viewed as complex domain, and also require the complex effort to support it. RUU AP has to esteem as part of bureaucracy reform effort in Indonesia. And to hope happened high acceleration in bureaucracy reform, hence RUU AP has to be supported with effort of developing commitment of public functionaries, developing system public service, improving the quality of human resource, improving exploiting of technology in bureaucracy (e-gov) and create best culture of bureaucracy. Key words: bureaucracy reform, public administration law, and culture of bureaucracy.